Measurement report: Exploring the variations in ambient BTEX in urban Europe and their environmental health implications - X. Liu; X. Zhang; M. Dufresne; T. Wang; L. Wu; R. Lara; R. Seco; M. Monge; A. M. Yáñez-Serrano; A. M. Yáñez-Serrano; A. M. Yáñez-Serrano; M. Gohy; et al. (Atmospheric Chemistry and Physics)
BTEX (benzene, toluene, ethylbenzene, and m-xylene,p-xylene, and o-xylene) are significant urban air pollutants. This study examines BTEX variability across 7 European countries using data from 22 monitoring sites in different urban settings (urban background, traffic, industry, and suburban background). Results indicate that the relative abundance of BTEX in urban areas follows the order toluene > benzene > m,p-xylene > o-xylene > ethylbenzene, with median mixing ratios of 266 ± 152, 163 ± 74, 129 ± 88, 53 ± 35, and 45 ± 27 ppt during the years 2017–2022, respectively. Seasonal trends show benzene had similar median concentrations across urban background, traffic, and industrial sites, indicating mixed sources. Toluene levels were highest in traffic and industrial areas, highlighting road traffic and industrial emissions. Ethylbenzene and xylenes showed equivalent levels in traffic and industrial areas but were lower in urban backgrounds. Peak BTEX levels occurred during morning and evening rush hours, linked to traffic, heating, and atmospheric stagnation. B/T<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="22pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="b95abee2c8564e01b32cbdbc660c6dc4"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-625-2025-ie00001.svg" width="22pt" height="14pt" src="acp-25-625-2025-ie00001.png"/></svg:svg> ratios ranged from 0.29 ± 0.11 to 1.35 ± 0.95, and X/E<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="2a5e97c90d0b1de015c17d7c93b47bc3"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-625-2025-ie00002.svg" width="23pt" height="14pt" src="acp-25-625-2025-ie00002.png"/></svg:svg> ratios ranged from 1.75 ± 0.91 to 3.68 ± 0.30, indicating primary pollution from local traffic, followed by solvents, coatings, and biomass burning. Lifetime cancer risk from BTEX exposure was below the definite risk threshold (10−4) but above the permissible risk level (10−6), suggesting moderate risk from benzene and ethylbenzene, particularly in traffic and industrial areas. Additionally, the health index of BTEX at monitoring sites was generally lower than the threshold limit value, suggesting a low non-carcinogenic risk overall. This study offers essential insights into BTEX pollution in urban European environments.